An "all-in-one" scaffold targeting macrophages to direct endogenous bone repair in situ. (15th July 2020) - Niu, Yiming; Wang, Lintao; Yu, Na; Xing, Panfei; Wang, Zhenzhen; Zhong, Zhangfeng; Feng, Yanxian; Dong, Lei; Wang, Chunming
Abstract: Scaffolds for tissue repair are designed in an increasingly complicated manner to meet multi-facet biological needs during the healing process. However, overly sophisticated design, especially the use of multiple components and delivery of exogenous cells, hampers the bench-to-bedside translation. Here, a multi-functional – yet mono-compositional – bioactive scaffold is devised to mediate the full-range, endogenous bone repair. Based on immunoactivity screening, a chemically-modified glucomannan polysaccharide is selected and processed into an anisotropic porous scaffold, which accurately stimulates macrophages to produce pro-regenerative cytokines. These cytokines effectively enhance the recruitment ("R") and induced osteogenesis ("IO") of the bone progenitor cells in situ . Meanwhile, the anisotropic porosity and carbohydrate signal of the scaffold facilitate differential adhesion ("A") and distribution ("D") of the macrophages and bone progenitor cells – enabling the former's accumulation at the surface while encouraging the latter's infiltration into the scaffold. Implanted in a rat calvarial defect model, this "RADIO" system effectively promotes healing over 12 weeks, with the obvious formation of hard callus through the scaffold. In summary, RADIO integrates multiple functions into one single scalable system ("all-in-one") to govern the dynamic bone-repair process, by harnessing the power of host macrophages. RADIO represents an open platform to solving the long-lasting complexity-versus-simplicity dilemma in biomaterials design. Statement of Significance: Biomaterials as versatile tools for tissue repair are becoming increasingly complicated, yet overly sophisticated design – especially the use of multiple components, exogenous cells, and overdosed growth factors – hampers their clinical application. The pre-requisite for designing a successful integrative scaffold is to identify an inherent biological target responding to biomaterial signals, thereby efficiently and safely promoting tissue repair via the endogenous healing capability instead of extra multifarious biochemical components. For bone regeneration, the pivotal regulator is macrophages. Through activating host macrophages, our single-component scaffold system coordinates the entire bone regenerative cascade in situ and induces successful bone regeneration in a calvarial defect model. This scaffold represents a scalable and multi-functional approach to effectively simplify the sophisticated design in regenerative medicine. Graphical abstract: Image, graphical abstract